Racial/Ethnic Disparities in Clinical Grading in Medical School. Issue 5 (20th October 2019) - Low, Daniel; Pollack, Samantha W.; Liao, Zachary C.; Maestas, Ramoncita; Kirven, Larry E.; Eacker, Anne M.; Morales, Leo S.
Abstract: Phenomenon: Performance during the clinical phase of medical school is associated with membership in the Alpha Omega Alpha Honor Medical Society, competitiveness for highly selective residency specialties, and career advancement. Although race/ethnicity has been found to be associated with clinical grades during medical school, it remains unclear whether other factors such as performance on standardized tests account for racial/ethnic differences in clinical grades. Identifying the root causes of grading disparities during the clinical phase of medical school is important because of its long-term impacts on the career advancement of students of color. Approach: To evaluate the association between race/ethnicity and clinical grading, we examined Medical Student Performance Evaluation (MSPE) summary words (Outstanding, Excellent, Very Good, Good) and 3rd-year clerkship grades among medical students at the University of Washington School of Medicine. The analysis included data from July 2010 to June 2015. Medical students were categorized as White, underrepresented minorities (URM), and non-URM minorities. Associations between MSPE summary words and clerkship grades with race/ethnicity were assessed using ordinal logistic regression models. Findings: Students who identified as White or female, students who were younger in age, and students with higher United States Medical Licensing Examination Step 1 scores or final clerkship written exam scores consistently received higher final clerkship grades. Non-URM minority students were more likely than White students (Adjusted Odds Ratio = 0.53), confidence interval [0.36, 0.76], p = .001, to receive a lower category MSPE summary word in analyses adjusting for student demographics (age, gender, maternal education), year, and United States Medical Licensing Examination Step 1 scores. Similarly, in four of six required clerkships, grading disparities ( p < .05) were found to favor White students over either URM or non-URM minority students. In all analyses, after accounting for all available confounding variables, grading disparities favored White students. Insights: This single institution study is among the first to document racial/ethnic disparities in MSPE summary words and clerkship grades while accounting for clinical clerkship final written examinations. A national focus on grading disparities in medical school is needed to understand the scope of this problem and to identify causes and possible remedies.